2016
DOI: 10.1037/cou0000158
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive predictors of academic and life satisfaction: Measurement and structural equivalence across three racial/ethnic groups.

Abstract: Data of 306 Caucasian American, 284 Asian American, and 259 Latino/a American college students were analyzed in this study to test a modified version of Lent and Brown's (2006, 2008) satisfaction model in the academic context. In addition to the full set of variables hypothesized in the original model, the modified academic satisfaction model also included independent and interdependent self-construals to represent one's cultural orientations. Comparisons between the hypothesized model and 2 alternative models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
9
35
0
Order By: Relevance
“…While personality traits and self-construal variables may be stable and less amenable to change, findings of this study suggested that environmental and person-cognitive variables, such as supports and self-efficacy, may offer possible mechanisms through which mental health and student affairs professionals can intervene to help Chinese college students maintain or improve their academic well-being. These findings are consistent with those derived from students in Taiwan and Singapore (Sheu et al, 2014), Portugal (Lent et al, 2012), Angola and Mozambique (Lent et al, 2014), as well as Asian American college students in the United States (Sheu, Mejia, Rigali-Oiler, Primé, & Chong, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…While personality traits and self-construal variables may be stable and less amenable to change, findings of this study suggested that environmental and person-cognitive variables, such as supports and self-efficacy, may offer possible mechanisms through which mental health and student affairs professionals can intervene to help Chinese college students maintain or improve their academic well-being. These findings are consistent with those derived from students in Taiwan and Singapore (Sheu et al, 2014), Portugal (Lent et al, 2012), Angola and Mozambique (Lent et al, 2014), as well as Asian American college students in the United States (Sheu, Mejia, Rigali-Oiler, Primé, & Chong, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The correlational pattern between the FFM dimensions and the academic and sociocognitive variables of GPA, academic self-efficacy, and academic satisfaction found in the present study is consistent with findings from previous research (e.g. McIlroy et al, 2015;Poropat, 2009;Sheu et al, 2016). This supports the construct validity of the dimensions 13 13 measured in the Danish IPIP-NEO-120.…”
Section: Discussionsupporting
confidence: 92%
“…McIlroy, Poole, Ursavas, & Moriarty, 2015); and academic satisfaction is generally positively associated with Extraversion and negatively associated with Neuroticism (e.g. Sheu, Mejia, Rigali-Oiler, Primé, & Chong, 2016). A replication of this correlational pattern in the present study would support the construct validity of the dimensions measured with the Danish IPIP-NEO-120.…”
supporting
confidence: 69%
“…Academic satisfaction also reflects how successfully a program is conducted ( Albarrak et al, 2013 ), which is closely related to student retention ( Wilkins-Yel et al, 2018 ). A few studies revealed that PYD qualities positively predicted academic satisfaction, including self-efficacy, emotional competence, and conscientiousness ( Lent et al, 2007 ; van Schaick et al, 2007 ; Sheu et al, 2016 ). Also, research studies revealed that PYD attributes such as hope and optimism predicted school satisfaction ( Wilkins et al, 2014 ; Sun, 2016 ).…”
Section: Introductionmentioning
confidence: 99%